KARAKTERISASI PADI LOKAL ASAL KECAMATAN KAMPAR TIMUR DAN KAMPAR UTARA KABUPATEN KAMPAR - Maharani Maharani; Elza Zuhry; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to determine the diversity of local rice accessions from East Kampar and North Kampar, Kampar District. This research was carried out at the Experimental Garden and Laboratory of Plant Cultivation, Faculty of Agriculture, University of Riau, Pekanbaru from September 2017 to March 2018 with descriptive analysis method, where there are 10 local rice accessions planted in pots . Each local rice accessions consists of five experimental sample units with a total of 50 units of data. The results of obtained character diversity of rice plants with all accessions has a drooping panicle shaft and medium criteria of plant age, 90% accession have a 2-cleft leaf tongue shape, 80% accessions has a high criteria plant height, 70% accessions has a panicle out shape with all panicle and neck panicle out, 60% local rice accessions have fertility of fertile grains, and 50% accessions has a long leaf character short criteria and the stem segment has a golden yellow color. Keywords: local rice, kinship, diversity, morphology, agronomy.